A roadmap for teaching in higher education: taking students and teachers on a journey - Duarte, Marina (2015)
In this paper, the metaphor of a “journey” is used to reflect on teaching and learning in Higher Education. Learning is seen as a “journey” where the guide is the teacher and the traveller is the student. Some key elements from the research done on the last decades are brought together in order to raise awareness to the complexity of this process, namely those regarding the teacher and the student, in order to help teachers begin to find the appropriate “journey” for themselves and their students. The ideas presented here are the result of a “teaching and learning journey” that the author took with a group of Professors of Higher Education Universities from Central Asia, in 2015.